A bibliometric analysis of exertional heat stroke research in Web of Science. Issue 1 (December 2016) - Mao, Zhi; Liu, Chao; Chen, Shuo; Zhu, Zheng-Guo; Kang, Hong-Jun; Zhou, Fei-Hu
Abstract Background Exertional heat stroke is a fatal condition and remains a health problem. This paper evaluates the publication trend regarding exertional heat stroke research between 1996 and 2015 using a bibliometric method. Method Articles regarding exertional heat stroke research published between 1996 and December 2015 were searched for in the SCI-EXPANDED database of Web of Science. The search results were analyzed with regard to publication year; publication quantity regarding countries/regions, and authors; citation frequency; and journal distribution. CiteSpace (v3.6) was used for a document co-citation visualization analysis. Results In total, 289 publications on heat stroke were located. After selection, 209 original articles conducted across 28 countries/regions and published in 83 journals were included in the analysis. The USA, Isreal, and France were the most common locations for exertional heat stroke studies. The CiteSpace visualization cluster analysis showed that exertional heat stroke-related mortality and protective measures were constant concerns of research. Conclusions Research related to exertional heat stroke has been continuous concerned. USA is still the leading country in this field.